Alterations of protein composition along the rostro-caudal axis after spinal cord injury: proteomic, in vitro and in vivo analyses - Cizkova, Dasa; Le Marrec-Croq, Françoise; Franck, Julien; Slovinska, Lucia; Grulova, Ivana; Devaux, Stéphanie; Lefebvre, Christophe; Fournier, Isabelle; Salzet, Michel (Frontiers in Cellular Neuroscience, 2014)
Based on proteomic analyses we investigated the differences of released molecules in the conditioned media (CM) from the spinal cord central lesion and adjacent rostral and caudal segments at 3, 7 and 10 days after spinal cord injury (SCI), in order to specify the molecular environment within greater extent of tissue damage. Proteins found in CM were analyzed by shot-gun MS using nanoLC coupled to an orbitrap. The results showed some specific proteins at each site of the lesion at 3days. Among the proteins from rostral and lesion segments, some are related to chemokines, cytokines or to neurogenesis factors. In contrast, proteins from caudal segments are more related to necrosis factors. The CM from each spinal segment were used in vitro, on microglial BV2 cell lines and DRGs explants, showing a lesion site-dependent impact on microglia activation and DRGs neurite outgrowth. In addition, while naive BV2 cells exhibited insignificant staining for CX3CR1 receptor, the level of CX3CR1 was strongly enhanced in some BV2 cells after their stimulation by CM collected from SCI. The molecular data might correlate with different polarization of activated microglia and macrophages along the rostro-caudal axis following acute injury. This was partially confirmed in vivo with CX3CR1 receptor, revealing higher expression in the rostral segment, with potential neuroprotective action. In addition, the neurotrophic factors released from rostral and lesion segments enhanced outgrowth of DRGs explants. Taken together these data suggest that regionalization in terms of inflammatory and neurotrophic responses may occur between rostral and caudal segments in acute SCI.